Retração total e penetração de cloretos em concretos com cimento Portland branco e escória de alto forno - Dellinghausen, Luciano de Medeiros (2009)
Drying Shrinkage is a phenomenon that occurs in concrete, subjected or not to a load, due to water loss, once exposed to environment and allowed to dry. It is responsible for almost the entire total shrinkage strain in concrete. A concrete element with restrained shrinkage deformation may develop tensions that cause cracks, allowing the ingress of aggressive agents that may cause some damage to the reinforcement, reducing, consequently, its strength and durability. The most common aggressive agent into concrete is the chloride ion, which is considered the great responsible for the early reinforcement corrosion of concrete structures, affecting its stability and durability. Corrosion of reinforcement bars due to the ingress of salts from sea water into concrete is recognized to be the most influent factor in the destructive mechanisms for marine structures. The use of mineral admixtures such as blast furnace slag, the increase of curing duration and the water/binder ratio reduction are measures that may reduce the chloride ion penetration. The aim of this study was to investigate the influence of the cement replacement content by slag, as well as the duration of curing on drying shrinkage, chloride ion penetration and compressive strength of concretes made with high early age strength cement and white Portland cement. Water-binder ratios of 0.30, 0.42 and 0.55, curing duration of 3 and 7 days, besides the cement replacement contents of 0%, 50% and 70% were investigated. In order to analyze the influence of the alkali activation on the properties investigated, a concrete made with 50% white Portland cement replacement content by slag and activated by sodium sulfate (4% in mass of binder) was used. The compressive strength was evaluated in the ages of 3, 7, 28 and 91 days; the drying shrinkage in the ages of 7, 14, 21, 28, 35, 56, 91 and 182 days, and the chloride ion penetration (immersion test in chloride solution) in the ages of 7, 14, 28, 56 and 91 days. Before being immersed in the chloride solution, the specimens were subjected to a drying period of 91 days. The results obtained revealed that an increase in the slag content decreased the compressive strength and the drying shrinkage values, besides the smaller depths of chloride penetration with both cements used. Reducing the curing duration resulted greater drying shrinkage and depth of chloride penetration for both cements, independently the slag content.